1982
DOI: 10.1063/1.329977
|View full text |Cite
|
Sign up to set email alerts
|

The improvement of fatigue life in Ti-6Al-4V by ion implantation

Abstract: The alloy Ti-6AI-4V has been implanted with carbon and nitrogen ions. The microstructure produced by these implants is found to contain fine particles of TiC and TiN respectively. Rotating beam fatigue tests show improved fatigue life for both implants, with the superior carbon implantation giving a 20% increase in endurance limit and a factor of 4-5 lifetime increase at higher stresses over unimplanted material. A dose of 1 X 10 17 at./cm 2 is required to obtain the maximum effect. Fatigue cracks have been ob… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
38
0
1

Year Published

1996
1996
2015
2015

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 154 publications
(39 citation statements)
references
References 11 publications
0
38
0
1
Order By: Relevance
“…In fact, Fig. 3 also includes literature data [30,33,34] for similar tests performed on samples having a mill-annealed microstructure and clearly, the results are inferior to all plasma treated variants. However, irrespective of the initial microstructure, better control of post-treatment cooling rate (from the a + b phase field) may be appropriate in order to optimise bulk microstructure.…”
Section: Fatigue Test Resultsmentioning
confidence: 95%
See 1 more Smart Citation
“…In fact, Fig. 3 also includes literature data [30,33,34] for similar tests performed on samples having a mill-annealed microstructure and clearly, the results are inferior to all plasma treated variants. However, irrespective of the initial microstructure, better control of post-treatment cooling rate (from the a + b phase field) may be appropriate in order to optimise bulk microstructure.…”
Section: Fatigue Test Resultsmentioning
confidence: 95%
“…Conversely, for samples which had been triode plasma diffusiontreated and tested in high cycle fatigue subsurface cracking could occur. It has also been reported that differences in the point at which crack initiation is related to the maximum bending stress applied and therefore the duration of the test [33]. More recently, Torres and Voorwald [50] suggested that, in low cycle fatigue, the high tensile load applied will always surpass any compressive residual stress present -thereby favouring surface cracking.…”
Section: Fracture Topographymentioning
confidence: 99%
“…A dose of 1 Â 10 17 ions/cm 2 was required to obtain the maximum effect. Fatigue cracks have been observed to originate up to 150 lm below the surface, indicating a complex interaction between the implanted layer and the fatigue failure process [123]. To combat high temperature (or service) fatigue Pt ion plating of the high temperature titanium alloys is also used [121].…”
Section: Fatigue Resistancementioning
confidence: 99%
“…INTRODUCTION 20 to 30 nm. [17] Carbon-implanted Ti6Al4V was annealed at different temperatures for 1 hour. [8] The TiC precipitates THE titanium alloy Ti6Al4V is used for load-bearing grow when the temperature exceeds 300 ЊC, reaching sizes components of joint prostheses.…”
mentioning
confidence: 99%